CHEMICAL CONTENT OF TURMERIC ;CURCUMIN AND ITS DERIVATIVES - Supardjan A. M. (Indonesian Journal of Pharmacy, 2001)
A brief review on turmeric from the stand-point of chemical content are presented. Recent studies on turmeric showed that at least 7 compounds of curcumin derivatives have been found, including cyclocurcumin the newer curcumin derivative.Keywords : curcumin, curcumin derivatives.